MENINGKATKAN RESILIENSI PESERTA DIDIK MELALUI METODE PROBLEM BASED LEARNING - Sutrisno, Bambang Sutrisno (JURNAL PENDIDIKAN ILMU SOSIAL, 2016)
The background of this study is the environmental conditions which are prevalent behavioral deviations and social background of students who come from low-income families, low education and family control is inadequate and learners need to have a level of resilience that is high in order to face the problems of their lives and avoid social deviation behaviors. The method employed in this research was Classroom Action Research, referencing the research design of Kemmis and Mc. Taggart, namely action research regarded as a spiral of the cycles of â€œPlan, Act, Observe, and Reflect,â€ which in this research were conducted in three cycles. Based on observations and analysis of the eight indicators of resilience, namely (1) Emotion Regulation; (2) Impulse Control; (3) Optimism; (4) Causal Analysis; (5) Empathy; (6) Self-efficacy; (7) Accomplishments; and (8) Faith and Spirituality, it is known that there is an increased resilience of learners after three cycles of actions, each consisting of two actions. In cycle I, the percentage of students with high resilience was 50%. An increase was observed in the second cycle, where the percentage of students with high resilience rose to 66.67%, and in cycle III all students acquired high resilience (100%). From this research it is known that the use of methods of problem based learning in social studies learning by taking the theme of social deviation can increase the resilience of learners.Keywords: Resilience, Problem Based Learning.